2008
DOI: 10.1017/s1138741600004169
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Intergroup Contact and the Role of Authorities in Prejudice Reduction

Abstract: The present study focuses on the effect of vicarious intergroup contact and the support of an authority figure on the improvement of outgroup and meta-stereotype evaluations. Meta-stereotype refers to the shared beliefs of ingroup members about how they consider outgroup members to perceive their group. Three preliminary studies were carried out to determine desirable and undesirable characteristics for a good basketball performance, the task that best demonstrates the application of these characteristics, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(42 citation statements)
references
References 41 publications
(67 reference statements)
2
38
0
2
Order By: Relevance
“…The small amount of work on mediated vicarious contact (none of it in the musical arena) shows that there are positive effects when people identify with the ingroup member in the contact experience, when the outgroup member is seen as somewhat typical of their group, and when the contact is positive (Gómez & Huici, 2008;Joyce & Harwood, 2014;Mazziotta, Mummendey, & Wright, 2011). These effects have been demonstrated not only with television stimuli, but also with children's story books (Cameron, Rutland, Brown, & Douch, 2006).…”
Section: Intergroup Contact Theorymentioning
confidence: 99%
“…The small amount of work on mediated vicarious contact (none of it in the musical arena) shows that there are positive effects when people identify with the ingroup member in the contact experience, when the outgroup member is seen as somewhat typical of their group, and when the contact is positive (Gómez & Huici, 2008;Joyce & Harwood, 2014;Mazziotta, Mummendey, & Wright, 2011). These effects have been demonstrated not only with television stimuli, but also with children's story books (Cameron, Rutland, Brown, & Douch, 2006).…”
Section: Intergroup Contact Theorymentioning
confidence: 99%
“…Research showed that imagined contact increases positive intergroup attitudes and perceptions of outgroup variability (Turner, Crisp, & Lambert, 2007a), enhances projection of positive traits to the outgroup (Stathi & Crisp, 2008), and reduces implicit prejudice (Turner & Crisp, 2010; Vezzali, Capozza, Giovannini, & Stathi, in press), and stereotype threat (Abrams et al, 2008; Crisp & Abrams, 2008). Alternative forms of indirect contact experiences are also promoted through media exposure (Herek & Capitanio, 1997; Ortiz & Harwood, 2007), ad hoc films (Gómez & Huici, 2008), and stories concerning intergroup contact (Cameron & Rutland, 2006).…”
Section: Indirect Forms Of Contactmentioning
confidence: 99%
“…The intervening variable was intergroup anxiety which was lower when contact was positive and higher when contact was negative. Vicarious contact is effective, as well: watching a video in which in-group and out-group members (basketball teams) performed cooperative activities decreased the perception that the in-group was negatively viewed by the out-group (Gómez & Huici, 2008) (for the effects of indirect exposure to the out-group on metaperceptions, see O 'Brien, Leidner, & Tropp, 2018).…”
Section: Humanity Metaperceptions and Intergroup Contactmentioning
confidence: 99%